Fitness – programs as mean of forming of personality physical culture of students - E.V. Kurmaeva (Physical Education of Students)
Basic directions of perfection of process of physical education of students of higher institutes are examined. Attention is accented on the necessity of search of new effective ways of making healthy of students, increases of level of their physical development and preparedness. A questionnaire inspection is conducted 150 students. It is set that 62% boys would prefer engaged in the power types of fitness (athletic gymnastics, power lifting) and 38% wished to be engaged in the traditional types of sport. 75% girls preferred a fitness (70% to the aerobic orientation, 5% - power), 25% girls were chosen by the traditional types of physical activity. It is shown classifications of fitness programs. It is suggested to adapt existent fitness is programs for employments in the institutes of higher. The possible ways of making healthy of students, increase of level of their physical development and preparedness, attaching to the active way of life are shown.